Ternary Semigroups Characterized by Spherical Fuzzy Bi-ideals - Nakkhasen, Warud; Chinram, Ronnason (Science & Technology Asia, 2023)
The concept of spherical fuzzy sets, was introduced by Ashraf et al. in 2019, and is a generalization of the concepts of intuitionistic fuzzy sets, picture fuzzy sets and Pythagorean fuzzy sets. In this paper, we introduce the concepts of spherical fuzzy quasi-ideals and spherical fuzzy bi-ideals of ternary semigroups and investigate some of their properties. Then, we characterize regular ternary semigroups in terms of spherical fuzzy left (resp., lateral, right) ideals, spherical fuzzy quasi-ideals and spherical fuzzy bi-ideals of ternary semigroups. Moreover, some characterizations of weakly regular ternary semigroups by the concepts of many types of spherical fuzzy ideals in ternary semigroups are discussed.